Inhibitory mechanism of vascular endothelial growth factor (VEGF) by bucillamine - Koyama, Shinji (2002)
1. Vascular endothelial growth factor (VEGF) plays an important role in the neovascularization of ischaemic retinal diseases such as proliferative diabetic retinopathy. We determined that bucillamine, an anti-rheumatic drug, inhibits the VEGF production induced by hypoxia in bovine retinal microcapillary endothelial cells (BREC). To further clarify the inhibitory mechanism, we investigated the possible mechanism by which bucillamine exerts this inhibitory effect. 2. Bucillamine (100 μM) decreased the hypoxia-induced increase of VEGF mRNA by 54.5% (P<0.001). Bucillamine (100 μM) reduced the hypoxia-induced VEGF content in culture media by 29.0% (P<0.001), while monosulfydryl drugs, N-acetylcysteine and D-penicillamine, did not. 3. Bucillamine (100 μM) did not affect VEGF mRNA half-life (hypoxia, 4.3 h; hypoxia+bucillamine, 3.9 h; normoxia, 2.7 h; normoxia+bucillamine, 2.7 h). 4. Reporter gene studies revealed that bucillamine reduced transcriptional activity in the 5′-flanking region of the VEGF gene by 74.0%. Hypoxia stimulated binding activity of BREC nuclear protein to a hypoxia responsive element (HRE), which was decreased by bucillamine. 5. Bucillamine inhibited hypoxic-induction of HIF-1α mRNA by 73.1% (P<0.001). Bucillamine also inhibited spontaneous VEGF mRNA expression by 26.6%. Furthermore, it inhibited activity of VEGF promoter and decreased binding activity to Sp1 and HRE, but did not alter AP1 and AP2 activity in normoxia. 6. These data suggest that bucillamine inhibits hypoxic induction of VEGF through inhibition of HIF-1 induction and binding activity in BREC. Bucillamine also inhibits the spontaneous expression of VEGF mRNA by its effect on Sp1 and HRE binding.